2022
DOI: 10.1182/blood.2021012743
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 3 trial of interferon-α vs hydroxyurea in polycythemia vera and essential thrombocythemia

Abstract: The goal of therapy for essential thrombocythemia (ET) and polycythemia vera (PV) patients is to reduce thrombotic events by normalizing blood counts. Hydroxyurea (HU) and interferon-α (IFN-α) are the most frequently used cytoreductive options for ET and PV patients at high-risk for vascular complications. Myeloproliferative Disorders Research Consortium 112 was an investigator-initiated, phase 3 trial comparing HU to pegylated IFN-α (PEG) in treatment naïve, high-risk ET/PV patients. The primary endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 17 publications
1
58
0
Order By: Relevance
“…28 In addition, a recent study found that longer treatment with peg-IFN was more effective in normalizing levels of blood cells and reducing driver mutation burden, while hydroxycarbamide produced more histopathologic responses. 19 Our study shows for the first time that hydroxycarbamide and peg-IFN lead to alterations in activation-dependent granule markers in platelets. The mechanism of action of these drugs is still not fully understood.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…28 In addition, a recent study found that longer treatment with peg-IFN was more effective in normalizing levels of blood cells and reducing driver mutation burden, while hydroxycarbamide produced more histopathologic responses. 19 Our study shows for the first time that hydroxycarbamide and peg-IFN lead to alterations in activation-dependent granule markers in platelets. The mechanism of action of these drugs is still not fully understood.…”
Section: Discussionmentioning
confidence: 59%
“…However, it remains unknown if the risk of thromboembolic events differs between ET patients treated with different cytoreductive drugs. Some studies indicate that the risk may differ, 9,10,17,18 whereas a recent phase 3 study found no differences 19 . However, the study was not powered to detect a difference in the rate of thromboembolic events between hydroxycarbamide and peg‐IFN treated high‐risk ET patients 19 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations